Association of serum biomarkers with early neurologic improvement after intravenous thrombolysis in ischemic stroke. - Yu Cui; Xin-Hong Wang; Yong Zhao; Shao-Yuan Chen; Bao-Ying Sheng; Li-Hua Wang; Hui-Sheng Chen (PLoS ONE, 2022)
Background Early neurologic improvement (ENI) after intravenous thrombolysis is associated with favorable outcome, but associated serum biomarkers were not fully determined. We aimed to investigate the issue based on a prospective cohort. Methods In INTRECIS study, five centers were designed to consecutively collect blood sample from enrolled patients. The patients with ENI and without ENI were matched by propensity score matching with a ratio of 1:1. Preset 49 biomarkers were measured through microarray analysis. Enrichment of gene ontology and pathway, and protein-protein interaction network were analyzed in the identified biomarkers. Results Of 358 patients, 19 patients with ENI were assigned to ENI group, while 19 matched patients without ENI were assigned to Non ENI group. A total of nine biomarkers were found different between two groups, in which serum levels of chemokine (C-C motif) ligand (CCL)-23, chemokine (C-X-C motif) ligand (CXCL)-12, insulin-like growth factor binding protein (IGFBP)-6, interleukin (IL)-5, lymphatic vessel endothelial hyaluronan receptor (LYVE)-1, plasminogen activator inhibitor (PAI)-1, platelet-derived growth factor (PDGF)-AA, suppression of tumorigenicity (ST)-2, and tumor necrosis factor (TNF)-α were higher in the ENI group, compared with those in the Non ENI group. Conclusions We found that serum levels of CCL-23, CXCL-12, IGFBP-6, IL-5, LYVE-1, PAI-1, PDGF-AA, ST-2, and TNF-α at admission were associated with post-thrombolytic ENI in stroke. The role of biomarkers warrants further investigation. Trial registration Clinical Trial Registration: https://www.clinicaltrials.gov; identifier: NCT02854592.